Cmentarzysko ludności kultury wielbarskiej z okresu rzymskiego w Brusach, stan. 11, gm. loco, woj. bydgoskie - Walenta, Krzysztof (Acta Universitatis Lodziensis. Folia Archaeologica, 1991)
In 1982 and 1986 year’s in Brusy, Jagiellońska st. 11 during earthwork was founding urn graves. The savework delived the next urn gravers. The most interesting graves aro no 3 with 2 bronze fibulas with silver plates A. V 130 and bronze buckle with semicircular frame ad grave no 5 with bronze filbula A. VI 168, fragment of second fibula the same type, silver clasp type В by J. Kmieciński and clay whorl. This equipment is dated on the turn of early and late Roman Period (phase B2/C1 ).